Pengembangan Lembar Kerja Mahasiswa (LKM) Terintegrasi Keterampilan Proses Sains (KPS) pada Materi Makrozoobentos - Rizky, Umar; Agustina, Tri Wahyu; Solikha, Maratus; Yuliawati, Astri (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This research aims to develop Student Worksheets (LKM) that integrate science process skills on macrozoobentos materials that are feasible and practical and improve students' science process skills. The research method used is R&D (Research and Development) with 3D model design (Define, Design, and Development). This research instrument consists of an expert validation questionnaire, a readability test questionnaire, a pre-test and post-test test to see the test to improve learning outcomes, and a student response questionnaire to assess practicality. The results of the study showed that expert validation consisting of material validation of 83% of the category was very feasible, media validation of 78% of the feasible category, validation of practitioners of teaching lecturers of 92% of the category was very feasible, and readability test of 88.9% of the category was very feasible. An increase in students' science process skills of 0.79 with a high n-gain criterion. The indicator planned experiments and used tools and materials had a high n-gain score. The student response results showed that the percentage of 90.5% was categorized as very good. The Student Worksheets developed are suitable for learning media and can improve students' science process skills in macrozoobentos materials in ecology practicum.